THE VECTOR OF DEVELOPMENT OF AMERICAN SOCIETY IN THE 21ST CENTURY: THE MELTING POT OR MULTICULTURALISM? (Revista Inclusiones, 2020)
The sociocultural policy of the United States was originally aimed at erasing ethnocultural and ethnolinguistic differences, persistently cultivating a unified American culture and values. Cultural uniformity was seen as the key to national unity and state-territorial integrity. In accordance with this, Americanization was taken as the basis of state policy at the beginning of the 20th century, which took the form of an educational campaign, in which English was given the role of the most important means of Americanization – the process of immigrant entry into American society. The purpose of the article is a comparative analysis of the concepts of “melting pot” and multiculturalism as ways to implement Americanization. Results of the study: The melting pot as one of the main paradigms of US ethnic development, formation of a single national identity, and cultural and biological mixing proved to be unrealizable due to racial discrimination and ethnic prejudices, while multiculturalism led to cultural and religious pluralism, which, as history shows, leads to many problems in society. The scientific novelty of the study is associated with a negative assessment of both ways of development of American society: neither of them led to an ideal result. Conclusions: What this vector will be like, depends on the welfare of the nation, nature of national-state education, US foreign policy, and its international relations. The prognosis for American society of the 21st century is as follows: the multicultural state of society with a predominance of Latin American traditions.